Frugivory, Post-feeding Flights of Frugivorous Birds and the Movement of Seeds in a Brazilian Fragmented Landscape - Pizo, Marco A. [UNESP]; dos Santos, Bruno T. P. [UNESP] (Wiley-Blackwell, 2011)
Habitat fragmentation can break down the movement processes of frugivorous animals, thus influencing the relationship between plants and their seed dispersers by altering the number and identity of seed dispersers, and their relative contribution to seed dispersal. We studied the assemblages of frugivorous birds, their composition, species richness, and visitation rates to fruiting plants growing in the different landscape elements (forest fragments, live fences, and trees isolated in pastures) embedded in a Brazilian fragmented, agricultural landscape. By following the post-feeding movements of frugivorous birds, we inferred the direction of seed movement from and to each of these landscape elements. Fruiting trees growing at different landscape elements were visited by frugivorous birds at similar rates. Isolated trees attracted a greater and distinct bird assemblage than trees in forest fragments or live fences. Judging by the post-feeding flights of birds, the seeds of isolated trees were the most likely to reach all the landscape elements considered, but the contribution of isolated trees to the seeds falling in forested habitats or pastures depended on their degree of isolation. A few bird species were able to move widely, visiting fruiting plants in all landscape elements, and promoting long-distance dispersal for plants. These few birds are of special interest because they are mobile links that connect habitats in fragmented landscapes with their seed dispersal services.
Keywords: Atlantic forest; bird movements; forest fragments; isolated trees; live fences; pastures